Features of student psychological well-being, self-organisation and motivation - L. V. Okonechnikova; E. E. Symanyuk; T. L. Foksha (Образование и наука)
Introduction. The article discusses the main approaches to the study of psychological well-being, gives a general idea of self-organisation and educational motivation as components of the leading educational and professional activity of students. Aim. The present research aimed to examine the levels of psychological well-being and their relationship with the motivation and self-organisation of students’ educational and professional activities. Methodology and research methods. The following methods were employed in the empirical study: Psychological Well-Being Scale developed by C. Ryff (adapted by N. N. Lepeshinsky), Self-Organisation of Activity (SOA) questionnaire by E. Y. Mandrikova, Style of Self-Regulation of Behaviour – SSRB-98 questionnaire by V. I. Morosanova, Motivation to Learn in Higher Education questionnaire by T. I. Ilyina, and Scale of Academic Motivation by T. O. Gordeeva, O. A. Sychev, and E. N. Osin. The Mann-Whitney U-test and the Spearman correlation coefficient (rs) were utilised to analyse the data. Results. Most undergraduate students exhibit an average level of psychological well-being, both on individual scales and in terms of the overall integral indicator. Low and high levels of well-being are characteristic of only a small portion of the sample. More than 90% of respondents demonstrate medium to high levels of self-organisation and self-regulation. Students are characterised by cognitive motivation, as well as motivation for self-development and achievement. External motivation, introjected motivation, and amotivation are minimally expressed among students. Scientific novelty. The study examines the features of motivation and self-organisation in the educational and professional activities of students with varying levels of psychological well-being. It also explores the relationship between psychological well-being and the self-organisation and motivation of students in their educational and professional pursuits. Practical significance. The results of the study offer valuable insights into modern students, which can be utilised to enhance the organisation of university education during the adaptation period and to implement a more individualised approach to student engagement.